A Scenario-Based Approach for Checking Consistency in User Interface Design Artifacts - Silva, Thiago Rocha Silva; Keywords, Author Keywords; Winckler, Marco Winckler (Teste; 2018: IHC_21, 2018)
Keeping the consistency of requirements in different artifacts along the development process is a cumbersome activity, especially if it is done manually. Previous studies have investigated the use of User Stories to write testable requirements in order to automate the assessment of a given set of development artifacts. This paper expands the research in this field describing a scenario-based approach for checking consistency in User Interface (UI) design artifacts, modeling business and user requirements. A case study is presented as a proof of concept showing how our approach could be used to ensure the consistency of both business and task models, besides UI prototypes and scenarios. Preliminary testing results have shown that our approach is able to identify even fine-grained inconsistencies in the mentioned artifacts, allowing establishing a reliable compatibility among different UI design artifacts.